PENGARUH TUNTUTAN ORGANISASI DAN DUKUNGAN KELUARGA TERHADAP BURNOUT KARYAWAN PADA PT. INOCYCLE TECHNOLOGY GROUP DI KABUPATEN GOWA - Muslim Nursalam Akhmad; Edi Jusriadi; M. Yusuf Alfian Rendra Anggoro KR (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2024)
This research aims to determine and analyze the influence of organizational demands on employee burnout, as well as to determine the influence of family support on employee burnout at PT. Inocycle Technology Group in Gowa Regency. The research method used is quantitative with validity and reliability tests as data analysis methods. The classic assumption test involves the data normality test, multicollinearity test, and heteroscedasticity test. Multiple linear regression analysis was used in this research, with hypothesis testing consisting of a partial significant test (t statistical test) and the determinant coefficient (R-Square). The research results show that organizational demands (X1) have a positive and significant influence on employee burnout at PT. Inocycle Technology Group in Gowa Regency. This means that if organizational demands are high, employee burnout levels will increase; conversely, if organizational demands are low, employee burnout tends to decrease. Family support (X2) turns out to have a negative and significant influence on employee burnout. In this context, a high level of family support can reduce the level of employee burnout, while a low level of family support can increase the level of employee burnout.